2019
DOI: 10.1097/rhu.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Medical Versus Surgical Approach to Initial Treatment in Septic Arthritis

Abstract: The results of the study show that initial surgical treatment in patients with native joint septic arthritis is not superior to IMT. However, half of the patients with shoulder and hip infections treated with IMT eventually required surgical intervention, suggesting that perhaps this should be the preferred initial approach in these cases.This is an open-access article distributed under the terms of the Creative Commons Attribution -Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
1
23
1
Order By: Relevance
“…A non-operative approach of NJSA management has not been yet prospectively studied. By contrast with Flores-Robles et al who did not observe worst outcomes with medical or surgical management, 29 in our cohort, patients undergoing surgery had higher rate of adverse joint outcome. However, we could not exclude an indication bias, since patients undergoing surgery probably had a more serious condition.…”
Section: Miscellaneouscontrasting
confidence: 99%
“…A non-operative approach of NJSA management has not been yet prospectively studied. By contrast with Flores-Robles et al who did not observe worst outcomes with medical or surgical management, 29 in our cohort, patients undergoing surgery had higher rate of adverse joint outcome. However, we could not exclude an indication bias, since patients undergoing surgery probably had a more serious condition.…”
Section: Miscellaneouscontrasting
confidence: 99%
“…In children with uncomplicated septic arthritis, as few as 10 days of antibiotic therapy may be sufficient [ 82 ]. Septic arthritis can be managed with antibiotics combined with joint drainage by arthroscopy, arthrocentesis, or arthrotomy [ 83 , 84 , 85 ]. Joint drainage decompresses the joint, improves blood flow, and removes bacteria, toxins, and proteases [ 84 ].…”
Section: Diagnosis and Treatment Of Septic Arthritismentioning
confidence: 99%
“…It is difficult to conclude whether this was due to serial aspiration having a therapeutic effect or, more likely, the presence of antibiotic therapy. Although the efficiency of treatment for septic arthritis may be debated, the length of treatment and thus inpatient hospital stay is not, with all previous research indicating a longer length of stay in medically managed septic arthritis [3,6,8], to which our series is no exception. In our case series, we used serial aspiration for one patient as a mode of palliative symptom control.…”
Section: Discussionmentioning
confidence: 79%
“…However, the medical management of septic arthritis is not a novelty, with good results being seen in treating native hip septic arthritis with serial aspiration in the paediatric population, and this remains a validated treatment option [ 5 ]. Recent research has indicated that in the adult population, the medical management of native joint septic arthritis is not inferior to surgical management [ 3 , 6 ] but has failed to demonstrate any patient outcome or cost advantages. Literature also fails to define a medical management timeline, particularly in regards to the timing of serial aspiration, the number of aspirates to be therapeutic, and objective measurements to assess the effectiveness of treatment.…”
Section: Discussionmentioning
confidence: 99%